Getting the Gospel right the tie that binds evangelicals together - Sproul, Robert Charles, 1939- (Grand Rapids, MI Baker, 1999)
Includes bibliographical references and indexes.
Keywords: Evangelicalism -- relations -- Catholic Church; Theology, doctrinal -- evangelical